HPLC-PDA VERSUS GC-MS IN THE ANALYSIS OF PARACETAMOL AND NON-STEROIDAL ANTI-INFLAMMATORY DRUGS IN WASTEWATER - HERGHELEGIU, Mihaela-Cătălina; ERNAULT, Aude; BELDEAN-GALEA, Mihail Simion; COMAN, Maria-Virginia (Studia Universitatis Babeș-Bolyai Chemia, 2023)
The widespread use of paracetamol and non-steroidal anti-inflammatory drugs (NSAIDs) make them increasingly present in environmental factors, especially in water. The aim of this work was to develop an accurate, precise and sensitive analytical procedure for the simultaneous determination of Paracetamol and four NSAIDs (Ketoprofen, Naproxen, Diclofenac, and Ibuprofen). To this aim, the extraction (liquid-liquid extraction, LLE, and solid-phase extraction, SPE) as well as the chromatographic (high-performance liquid chromatography-photodiode array detector, HPLC-PDA, and gas chromatography-mass spectrometry in selected ion monitoring mode, GC-MS-SIM) techniques, in terms of the performances were compared. Different extraction solvents and types of cartridges at pH 3 of samples were tested for the extraction optimization. Low limits of detection and quantification at the g/L level were achieved. The developed HPLC-PDA and GC-MS-SIM methods were applied to the analysis of selected pharmaceuticals in different wastewater samples.